The treatment with antibody of TNF-? reduces the inflammation, necrosis and fibrosis in the non-alcoholic steatohepatitis induced by methionine- and choline-deficient diet - Koca, Suleyman Serdar; Bahcecioglu, Ibrahim Halil; Poyrazoglu, Orhan Kursat; Ozercan, Ibrahim Hanifi; Şahin, Kazım; Ustundag, Bilal (Springer/Plenum Publishers, 2008)
To assess the effects of anti-TNF-alpha antibody (infliximab) in experimental steatohepatitis induced by methionine- and choline-deficient (MCD) diet. The study included thirty rats. One group received normal rat food, and two groups received MCD diet. The treatment group received a single dose intra-peritoneal infliximab (4 mg/kg), at week 8. MCD diet increased levels of AST, ALT, TNF-alpha, TGF-beta(1), tissue and plasma MDA (p < 0.05 for each). Moreover, it led to steatosis, ballooning degeneration, inflammation, fibrosis and increased actin expression, histopathologically (p < 0.05 for each). In this experimental steatohepatitis anti-TNF-alpha antibody decreased the levels of AST, ALT, TGF-beta(1) and plasma and tissue MDA (p < 0.05 for each). Moreover, inflammation, necrosis, actin expression and fibrosis decreased in anti-TNF-alpha group compared to placebo group (p < 0.05 for each). This study indicates that anti-TNF-alpha antibody is effective on necrosis, inflammation and fibrosis in the experimental model of non-alcoholic steatohepatitis, induced by MCD diet.
Keywords: steatohepatitis; methionine- and choline-deficient diet; infliximab